Structure-property-processing correlations of longitudinal freeze-cast chitosan scaffolds for biomedical applications. (September 2021) - Yin, Kaiyang; Divakar, Prajan; Wegst, Ulrike G.K.
Abstract: Needed for the custom-design of longitudinally freeze-cast chitosan scaffolds for biomedical applications are systematic structure-property-processing correlations. Combining mechanical testing in compression with both scanning electron microscopy and semiautomated confocal microscopy for a quantitative structural characterization of fully hydrated chitosan scaffolds, robust correlations were determined. Decreasing the applied cooling rate from 10 °C/min to 0.1 °C/min, the short and long axes of the pore cross-sections, the pore aspect ratio, and the pore area were found to increase from 68.0 μm to 120.5 μm, from 189.2 μm to 401.2 μm, from 2.64 to 3.52, and from 8, 922 μm 2 to 35, 596 μm 2, respectively. Values for the scaffolds' modulus, yield strength, and toughness range from 1, 067 kPa to 3, 209 kPa, from 37.7 kPa to 75.5 kPa, and from 20.3 kJ/m 3 to 35.3 kJ/m 3, respectively. Because of additional structural features, such as cell wall stiffening ridges, affecting the mechanical properties, not linear but more complex correlation with modulus, yield strength, and toughness were observed. Contrasting the results of this study with those obtained in an earlier study of dry and fully hydrated collagen scaffolds, we were able to identify features that are important and peculiar to each material system. Highlighted in this study are newly determined robust structure-property-processing correlations as well as processing conditions and features that are critical for the mechanical performance of chitosan and other biopolymer scaffolds made by freeze casting for biomedical applications.